COMPARISON OF PHONETIC ASPECTS OF THE WORDS IN ENGLISH AND UZBEK LANGUAGES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation:This article presents a comparative analysis of the phonetic aspects of words in English and Uzbek languages. It specifically explores the pronunciation of sounds in both languages, highlighting similarities and differences in how sounds are articulated and their acoustic properties. Additionally, the article addresses common pronunciation errors made when attempting to pronounce English vowels and consonants.